Exploiting carbonyl groups to control intermolecular rhodium-catalyzed alkene and alkyne hydroacylation - Coxon, TJ; Fernández, M; Barwick-Silk, J; Mckay, AI; Britton, LE; Weller, AS; Willis, M (American Chemical Society, 2017)
Readily available β-carbonyl-substituted aldehydes are shown to be exceptional substrates for Rh-catalyzed intermolecular alkene and alkyne hydroacylation reactions. By using cationic rhodium catalysts incorporating bis-phosphine ligands efficient and selective reactions are achieved for β-amido, β-ester and β-keto aldehyde substrates, providing a range of synthetically useful 1,3-dicarbonyl products in excellent yields. A correspondingly broad selection of alkenes and alkynes can be employed. For alkyne substrates, the use of a catalyst incorporating the Ampaphos ligand triggers a regioselectivity switch, allowing both linear and branched isomers to be prepared with high selectivity in an efficient manner. Structural data confirming aldehyde chelation, and a proposed mechanism, are provided.